Restructuring Of Students’ Thinking in Junior High School Through Defragmentation for Solving Mathematical Problems - Liny Mardhiyatirrahmah; Abdussakir Abdussakir (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
Problem-solving in math is still a problem today. Studies show that students still make mistakes in answering math problems. Errors in answering the questions indicate that there is fragmentation in the thinking structure of students. This article uses a systematic review method. Researchers selected articles according to the criteria and found 9 articles with a total of 25 research subjects. Data collection was carried out in two main stages, namely the search and selection stages. The results show that students experience many obstacles at the stage of re-checking the integrity of the completion steps because of the habit of students who skip the re-examination and are sure that the answer is correct. A common type of error in the construction of a mathematical concept is a construction hole. Construction holes can be overcome by the emergence of schemes to complement the imperfections of students' thinking structures in solving mathematical problems. The type of defragmentation that is most often given is scaffolding. Scaffolding is considered the most effective for all types of mistakes made because it can be done and later reduced so that students can solve math problems independently.